Development of Android-Based Learning Media Applications to Determine Validity and Feasibility for Grade VII Middle School Students on Ecosystem Material - Ima Aryani*; Dias Aziz Pramudita; Nizar Nauli Sinangkling; Ifan Destya Adi Tama (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
The world community has been hit hard by the covid-19 outbreak since 2 years ago until now there are still confirmed cases with a new variant. This also has an impact on the world of education, so that all learning implementers compete to create innovative learning media, easy to apply using mobile phones both online and offline in supporting the process and understanding of student material. The research objective is to develop an android-based learning media application. The development method is using the waterfall process model which is divided into six stages, namely: communication, planning, modeling, construction, and deployment. The assessment aspect observed in the development of learning media is how the media is developed and the teaching materials contained in it. The results of the assessment through filling out instruments on learning media were developed using a scale of 4 from various aspects of observation by experts in their fields, namely: 1) Media expert validators, namely: (a) software engineering aspects 3.75; (b) aspects of learning design 3.71; and (c) visual communication aspect 3.77; 2) Validators of material experts and teachers, namely: (a) aspects of learning objectives 4; (b) aspects of learning materials 3.95; (c) aspects of learning methods 3.5; (d) aspects of learning resources 3.5; and (e) aspects of learning activities 3.75. From this assessment, it can be concluded that the developed learning media has a good predicate and is suitable for use in the learning process